Kant in Finland - Vaha, Milla; Laiho, Hemmo; Nikkarla, Markus (Con-Textos Kantianos. International Journal of Philosophy, 2020)
In the editorial note, we shortly outline the reception of Kant’s philosophy in Finland and how Kant’s philosophy became an academic topic from the late 18th century onwards. We also provide some details about the translations of Kant’s works into Finnish. Finally, we introduce the contributions to the special section on Kantian studies in Finland.